Culture of Mycobacterium kansasii in the blood of an HIV negative patient. Issue 6 (June 1993) - Veale, D; Fishwick, D; White, J E; Gascoigne, A D; Gould, K; Corris, P A
Abstract : A 23 year old man with a congenital myelodysplastic disorder and fibrosing lung disease received treatment with prednisolone. After nine months his condition deteriorated and Mycobacterium kansasii was isolated from blood cultures and lymph node biopsy specimens. He responded to antituberculous treatment. M kansasii has not previously been isolated from the blood stream of HIV negative patients.